Implementation of System Digitalization in Payment and Deposit of Non-Tax Revenue from Minerals and Coal Resources - Situmorang, Dokman Marulitua; Al-Afgani, Faisal Jamaludin (The Graduate School of Sahid University, 2023)
State revenue consists of three components, namely tax revenue, non-tax state revenue, and grants. The Financial Report of the Central Government Financial Supervisory Agency (audited) for Fiscal Year 2019, shows a contribution of Non-Tax State Revenue of 20.8 percent of total state revenue, so Non-Tax State Revenue is a significant component of state revenue to finance state spending that is not sufficiently financed from tax and grant receipts. In order to optimize the management of Non-Tax State Revenue, in 2014 an accurate, fast, and accountable, web-based (integrated) information system was introduced to support the management of Non-Tax State Revenue known as the Online Non-Tax State Revenue Information System (â€œSIMPONIâ€). However, for Non-Tax State Revenues for Natural Resources specifically for minerals and coal, there is still potential for improvement in terms of accountability and accuracy of calculations, so in 2019 a special information system was introduced for Non-Tax State Revenues for Natural Resources specifically for minerals and coal called â€œe-PNBP Minerbaâ€ integrated with â€œSIMPONIâ€.